Successful Management of a Rare Distant Endodontic Lesion: A Case Report - Eghbal, Mohammad Jafar; Parhizkar , Ardavan; Asgary, Saeed (Iranian Endodontic Journal, 2024)
The current case report aims to document a rare presentation of a distant odontogenic lesion of a 35-year-old male patient with mild clinical discomfort in the mandibular right first molar; exploring the diagnostic and therapeutic intricacies of an uncommon distant endodontic pathosis ultimately resolved through meticulous nonsurgical retreatment. Despite a normal oral examination, diagnostic radiography revealed a suboptimal root canal treatment and apical lesions surrounding mesial- and distal-root apices; including a distinct radiolucency beneath the apex of the second mandibular molar discovered through panoramic radiography, and confirmed via cone-beam computed tomography. In addition, the computed tomography disclosed a previously unreported and unusually large endodontic lesion that extended toward the mandibular canal; highlighting a necessity for the continued exploration of a unique endodontic presentation. A nonsurgical endodontic retreatment led to a remarkable reduction in the radiolucent lesions within one year; emphasizing the significance of comprehensive diagnostic approaches and individualized treatments.